PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING PADA MATA PELAJARAN PENDIDIKAN AGAMA HINDU DAN BUDI PEKERTI SISWA KELAS IX DI SMP NEGERI 3 DENPASAR : Pendahuluan, Metode, Hasil dan Pembahasan, Kesimpulan - Wisnu Murti, Yuga; Anggreni, Ni Made; Aryatnaya Giri, I Putu Agus (Guna Widya: Jurnal Pendidikan Hindu, 2026)
The learning model used in teaching and learning activities must align with the spirit of the Independent Curriculum, which emphasizes independent learning and contextual problem-solving. This study aims to describe the implementation of the Problem-Based Learning (PBL) model, identify obstacles and analyze efforts made to overcome them, and assess the impact of PBL implementation on learning quality. This study used a qualitative approach with descriptive methods. The results show that the implementation of the PBL model was carried out through the stages of contextual problem presentation, group discussion, investigation, presentation, and reflection, with the teacher acting as an active facilitator. Obstacles encountered included time constraints, differences in student abilities, and limited learning resources. Efforts made included adjusting schedules, providing group guidance, and procuring additional teaching materials. In general, the implementation of PBL had a positive impact on increasing student engagement, critical thinking skills, collaboration, and strengthening Hindu spiritual values ​​in students' daily lives.